A single-stage AC-DC-AC buck-boost converter with variable frequency operations for power quality. Issue 3 (3rd July 2021) - Zahra, Shabab; Hussain, Jawad; Akram, Muhammad Mubasher; Siddique, Muhammad
ABSTRACT: This paper presents a new direct ac-ac converter topology with new switching techniques and step-changed frequency operations. However, the existing traditional ac-ac converters suffer from two-stage power processing, ac-dc-ac, large dc-link electrolytic capacitor, modulation indices constraints, and complex control. The proposed converter provides symmetric non-inverting and inverting buck-boost operating modes with bipolar voltage and step-change frequency which can compensate broad range of voltage sag and swell without commutation and shoot through problem. Furthermore, the proposed operations minimise the dc-link capacitance requirement (<10 μF), and thus, film capacitor can be employed with high reliability and low loss and less switches. The proposed operating mode when use with dynamic voltage restorer work under entire power factor range and is suitable for reactive load. A detailed analysis using Sabre simulation and experimental results is presented.